3-Pyridyl Substituted Aliphatic Cycles as CYP11B2 Inhibitors: Aromaticity Abolishment of the Core Significantly Increased Selectivity over CYP1A2 - Yin, Lina; Hu, Qingzhong; Hartmann, Rolf W. (PLOS ONE, 2012)
Aldosterone synthase (CYP11B2) is a promising therapeutic target for the treatment of cardiovascular diseases related to abnormally high aldosterone levels. On the basis of our previously identified lead compounds I–III, a series of 3-pyridinyl substituted aliphatic cycles were designed, synthesized and tested as CYP11B2 inhibitors. Aromaticity abolishment of the core was successfully applied to overcome the undesired CYP1A2 inhibition. This study resulted in a series of potent and selective CYP11B2 inhibitors, with compound 12 (IC50 = 21 nM, SF = 50) as the most promising one, which shows no inhibition toward CYP1A2 at 2 µM. The design conception demonstrated in this study can be helpful in the optimization of CYP inhibitor drugs regarding CYP1A2 selectivity.